STRATEGI DINAS KOPERASI, UMKM, & TENAGA KERJA KOTA PALU DALAM MEMBERDAYAKAN USAHA MIKRO DI PASAR INPRES MANONDA PALU - Syaakir Sofyan; Ahmad arief (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
This paper discusses "the strategy of cooperative service, UMKM, and labor force of Palu in empowering micro business in market of Inpres Manonda Palu". The purpose of this paper is to find out the strategic steps of Cooperative service and UMKM of Palu City in empowering micro business in market of Inpres Manonda Palu, The results of this study show the general picture of micro business in market of Inpres Manonda Palu is the number of business actors as many as 1040 traders are recorded on Market Office with the largest number of traders is mixture of merchants / agricultural products totally 205 trades. All the needs of society generally can be fulfilled in market of Inpres Manonda Palu. The dominant tribe is the Buginese tribe. The strategic steps of cooperative service, UMKM, and labor force of Palu City have been implemented through the planning, implementation and evaluation process based on the 5th Annual Plan. The steps that have been implemented are data collection, product marketing through e-commerce, socialization, formation of cooperatives, training, construction of partnership network.